2022
DOI: 10.3389/fonc.2022.846568
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Shear Wave Elastography in the Diagnosis of Breast Cancer Axillary Lymph Node Metastasis and Its Correlation With Molecular Classification of Breast Masses

Abstract: ObjectiveTo explore the diagnostic value of shear wave elastography examination (SWE) on axillary node metastasis (ANM) in breast cancer, this study aimed to evaluate the correlation between the SWE features and different molecular types of breast cancer, and to check the elastic modulus differences among the molecular types.MethodsBreast cancer patients from November 2020 to December 2021 were subjected to both conventional ultrasonic examination (CUE) and SWE before ultrasound-guided percutaneous biopsy or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The ALNM status of breast cancer is important for clinical decision-making and prognosis of patients. Conventional ultrasound evaluation of ALN is mainly based on the aspect ratio, absence of fat gates, heterogeneous cortical thickening, and peripheral or mixed blood flow type ( 13 , 14 ), but previous studies ( 15 - 17 ) have reported conventional ultrasound to be insufficient for the preoperative evaluation of ALNM, with the sensitivity ranging from 35% to 82% and the specificity ranging from 73% to 97.9%. The sensitivity and specificity for predicting high nodal burden in this study were 70.15% and 61.82%, respectively, which was consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…The ALNM status of breast cancer is important for clinical decision-making and prognosis of patients. Conventional ultrasound evaluation of ALN is mainly based on the aspect ratio, absence of fat gates, heterogeneous cortical thickening, and peripheral or mixed blood flow type ( 13 , 14 ), but previous studies ( 15 - 17 ) have reported conventional ultrasound to be insufficient for the preoperative evaluation of ALNM, with the sensitivity ranging from 35% to 82% and the specificity ranging from 73% to 97.9%. The sensitivity and specificity for predicting high nodal burden in this study were 70.15% and 61.82%, respectively, which was consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…This favorable prognostic impact of YAP1 expression was also seen in the public datasets analyses, which showed significant superior survival in high-YAP1 group of IHC-defined ER+ breast cancer. Recently, several studies regarding the Hippo signaling pathway and ERα regulation suggested the inhibitory role of YAP1 on ER+ breast cancer growth [36][37][38]. In ER+ breast cancer cell lines, LATS1/2, upstream inhibitors of YAP1, are required to maintain ER+ cancer cell growth while little effect was observed in ER− cancer cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 7776 patients (range, 42-313) were included in 22 studies (3,10,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), all of whom were pathologically confirmed to have lymph node metastases of breast cancer. Among these studies, there were 2 retrospective studies and 20 randomized controlled studies.…”
Section: Study Characteristicsmentioning
confidence: 99%